Identificando sinalizações referentes às expectativas de aprendizagem sobre geometria, ao término da educação básica - Silva, Benedito Cardoso da (2004)
This current paper aims at investigating issues concerning the expectations of Geometry learners after they go through the four years of High School. Thus, its intention is to contribute with the general reflections on the teaching of Geometry throughout that same period. It also tries to approach new curriculum contents (proposals) and their trend, and analyses the questions (tests) proposed in some vestibulares ( College Admission Tests) in the State of São Paulo and in the National Testing System for High Schools (Exame Nacional do Ensino Médio-ENEM).These two major Testing Systems, as we know, are determining factors to define projects for Geometry teaching in High School. This paper also seeks to investigate the characteristics that shape the proposals for Geometry teaching at Elementary School, the directions that vestibulares and ENEM are moving towards and which areas of Geometry have been mostly tested.Our purpose is to examine possible consequences that these recent trends may have on the teaching of Geometry throughout Elementary School. This paper makes use of bibliography and documentation research to offer an evaluation of the most frequent questions (tests) that were presented by ENEM and vestibulares in their 2001-2003 issues. The main results of our study show that vestibulares tend to focus on a limited group of contents and abilities, giving little attention to contextual and interdisciplinary situations, which, nevertheless, are the main characteristic of the tests proposed by ENEM. Therefore, taking into account the trends analyzed, we conclude that the vestibulares fail to meet the expectations of Geometry learners at the end of High School